Modeling Method of the Grey GM(1, 1) Model with Interval Grey Action Quantity and Its Application. (31st January 2020) - Zeng, Bo; Ma, Xin; Shi, Juanjuan
Abstract : GM(1, 1) is a univariate grey prediction model with incomplete structural information, in which the real number form of the simulation or prediction data does not conform to the Nonuniqueness Principle of Grey theoretical solution. In light of the network model of GM(1, 1), the connotation of grey action quantity is systematically analyzed and the interval grey number form of grey action quantity is restored under uncertain influencing factors. A novel GM(1, 1) model is then constructed. The new model has the basic characteristics of the grey model under incomplete information. Moreover, it can be fully compatible with the traditional GM(1, 1) model. The developed model is employed to the natural gas consumption prediction in China, showing that its predicting rationality is much better than that of the traditional GM(1, 1) model. It is worth mentioning that, for the first time, the grey property of GM(1, 1) has been restored in structure, which is of significance for both academia and industry.